Contextualizing teacher motivation research. (December 2021) - Usher, Ellen L.
Abstract: At the heart of the social cognitive theoretical approaches common to all papers in this special issue is a recognition that the contexts in which teachers live and work affect their level of motivation, how they feel, and what they do. Teacher motivation, in turn, can affect students' perceptions and behaviors. This commentary addresses the major contributions made by the papers in this special issue toward advancing a more contextualized understanding of teacher motivation. Contextual considerations include theoretical and practical interpretations, sampling, the teaching and learning setting, measurement, and study design and analyses. Recommendations are offered for how researchers can better account for the role of context in all aspects of teacher motivation research.